MobileMed A PDA-Based Mobile Clinical Information System. - Jinwook Choi (IEEE Transactions on information technology in biomedicine)
Patient clinical data are distributed and often fragmented in heterogeneous systems, and therefore the need for information integration is a key to reliable patient care. Once the patient data are orderly integrated and readily available, the problems in accessing the distributed patient clinical data, the well-known difficulties of adopting a mobile health information system, are resolved. This paper proposes a mobile clinical information system (MobileMed), which integrates the distributed and fragmented patient data across heterogeneous sources and makes them accessible through mobile devices. The system consists of four main components: a smart interface, an HL7 message server (HMS), a central clinical database (CCDB), and a web server. The smart interface and the HMS work in concert to generate HL7 messages from the existing legacy systems, which essentially send the patient data in HL7 messages to the CCDB to be stored and maintained. The CCDB and the web server enable the physicians to access the integrated up-to-date patient data. By proposing the smart interface approach, we provide a means for effortless implementation and deployment of such systems. Through a performance study, we show that the HMS is reliable yet fast enough to be able to support efficient clinical data communication